Constitutional History During the Parliamentary System of Government: Ris to Presidential Decree (1949-1959) - Suciyati, Putri Hasri; Zulkarnain, Zulkarnain (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2024)
The purpose of this article is to find out the history of state administration during the parliamentary system of government, starting from the time of the United Republic of Indonesia (RIS) to the Presidential Decree (1959), which made Indonesia return to the form of a republic. This article uses the historical method with the stages of gathering sources, verifying, discovering, and writing. The results obtained based on the collection of sources and data show that the parliamentary system of government during the time of the United States of Indonesia lasted very briefly, namely from 19491950, using the RIS Constitution as a legal guide. Then, still using a parliamentary system of government, Indonesia returned to the form of the Republic of Indonesia, but with the 1950 Constitution as a legal guideline. This law was drafted by combining the 1945 Constitution and the RIS Constitution. The Unitary State of the Republic of Indonesia with the 1950 Constitution lasted quite a long time, until finally the government in Indonesia with a parliamentary system of government ended when the Presidential Decree was issued in 1959.